The Existence of Pancasila in the Draft Law on the Direction of Pancasila Ideology (Sociolegal Study on Public Response to Law Enforcement) - Roys Qaribila (Jurnal Indonesia Sosial Teknologi, 2024)
Pancasila as the basis of the Indonesian state has an important role in national and state life. However, along the way, Pancasila experienced various challenges and dynamics, including the emergence of the Pancasila Ideology Policy Bill (RUU HIP) which sparked pros and cons in society. This research aims to analyze the existence of Pancasila values in the Draft Law on Pancasila Ideology and formulate the public's response to the enactment of the resulting law. The method in the research uses a qualitative approach by collecting data through literature studies. After the data is collected, it then involves analysis techniques through three steps, namely simplifying information, presenting data findings, and drawing conclusions. The findings of the research show that supporters of this bill argue that aligning the law with Pancasila values will strengthen the state's ideological foundation and ensure that the nation's noble values become the basis for all activities. However, on the other hand, critics highlight several controversial aspects of this bill that the interpretation of the trisila in the HIP Bill is not in line with the version of Pancasila that is widely accepted by Indonesian society. In addition, the absence of an MPRS regulation regulating the dissolution of the PKI in the bill raises concerns that the removal of this reference could give the impression that the government does not recognize the history of the dissolution of the PKI, which is considered an important moment in Indonesian history. Apart from that, there are concerns that this bill could be misused for certain political interests which could damage social harmony and stability in Indonesia.